Educational strategies for the academic motivation of university students. A systematic review - Jessica Quito Calle (Perspectivas Metodológicas​)
The present work proposes to carry out a systematic review on educational strategies for the academic motivation of university students. Following the criteria established by the PRISMA Statement, the systematic review was carried out in January 2024 that, of the 674,421 articles identified, only six met the established inclusion criteria. The articles come from five databases that refer to publications in English and Spanish between 2023 and early 2024. It is concluded that the best educational strategies are accompanied by computer programs. At the same time, environmental support, an adequate self-concept and intrinsic motivation are the key to the academic success of university students.